(untitled) (Economics and region, 2025)
The paper examines the socio-economic efficiency of low-code platforms in higher education digital marketing in Ukraine. Based on a systematic literature review and functional analysis of leading low-code/no-code (LCNC) platforms (Bubble, Adalo, Tilda, Microsoft Power Apps, Make.com), three implementation scenarios are proposed for institutions at different digital maturity levels. A quantitative evaluation methodology (cost savings, conversion changes, time-to-market) is presented and illustrative calculations are provided for each scenario. Findings indicate that with adequate information security and IT governance, low-code solutions significantly increase marketing effectiveness and reduce development costs in the short term. The paper offers practical recommendations for HEI leadership and marketing teams on platform selection, process organization, and risk mitigation.